WASHBACK OF THE ENGLISH SECTION OF COLLEGE ENTRANCE EXAM ON THE STUDENTSâ PRODUCTIVE AND RECEPTIVE SKILLS - Wulandari, Fitri Wulandari (STKIP Muhammadiyah Pringsewu, 2016)
Exam plays a powerful role in educational system and exerts significant washback onstudentsâ learning. Washback, the impact of exams on education in general andlanguage examining in particular, has become a popular area of study withineducational research. This paper focuses on the washback effects of college entranceexam on studentsâ productive and receptive skills in STKIP MuhammadiyahPringsewu Lampung. The main concern of the study was to investigate the impact ofcollege entrance exam on productive and receptive language skills in STKIPMuhammadiyah Pringsewu Lampung. 53 first year students at English EducationDepartment in the academic year of 2015-2016 of STKIP Muhammadiyah PringsewuLampung attended the study. A 26-item questionnaire was designed and administeredto 53 students. The data were analyzed using statistical analysis including descriptivestatistics (frequency, percentage, mean, and standard deviation). It has been found outthat the exam has some negative effects on studentsâ language productive andreceptive skills on the first year students at English Education Department of STKIPMuhammadiyah Pringsewu Lampung. Some changes to exam that might be gratefulare discussed in the last section of the paper.Keywords: washback effect, college entrance exam, studentsâ productive skills